Preparation method and application of electrochemical chiral sensor material L-Ni-BDC / NM88B (Fe) based on chiral MOF-on-MOF heterostructure

By preparing Ni-BDC and NH2-MIL-88B(Fe) heterostructures and introducing chiral cysteine ​​modification, the selectivity and stability issues of single MOF materials in chiral recognition were solved, and efficient L/D-tryptophan recognition was achieved.

CN121086255APending Publication Date: 2025-12-09SHANDONG BAOLONGDA NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511192451.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-25
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Existing single MOF materials have limitations in terms of selectivity, sensitivity, and stability in the field of chiral recognition, and the preparation methods and performance optimization of MOF-on-MOF heterostructures are not yet mature.

Method used

A hydrothermal method was used to prepare Ni-BDC coupled with NH2-MIL-88B(Fe) to form a MOF-on-MOF heterostructure. By introducing chiral cysteine ​​to modify the structure, a stable Ni-O-Fe bond was formed, and L-Ni-BDC/NM88B(Fe) material was prepared.

Benefits of technology

The electron transfer capability and chiral recognition efficiency of the material were improved, and efficient recognition of L/D-tryptophan was achieved with a recognition efficiency of 3.05.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121086255A_ABST
    Figure CN121086255A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an electrochemical chiral sensor material L-Ni-BDC / NM88B (Fe) based on a chiral MOF-on-MOF heterostructure, and belongs to the technical field of electrochemical chiral sensing recognition materials. According to the technical scheme, the preparation method comprises the following steps: firstly, dissolving ferric chloride hexahydrate and 2-aminoterephthalic acid in an alkaline solution, and carrying out hydrothermal reaction to prepare NH2-MIL-88B (Fe); and then the NH2-MIL-88B (Fe) is dissolved in an acid solution containing terephthalic acid and nickel chloride hexahydrate, and the composite material Ni-BDC / NM88B (Fe) is prepared through a hydrothermal reaction. And continuously adding EDC and NHS to activate carboxyl of TPA, then adding a protonated cysteine solution, and carrying out an amidation reaction to prepare a target product. A sensor prepared from the material prepared by the invention can quickly and sensitively identify L-tryptophan in tryptophan isomers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical chiral sensing and recognition materials technology, specifically relating to the preparation method and application of an electrochemical chiral sensor material L-Ni-BDC / NM88B(Fe) based on a chiral MOF-on-MOF heterostructure. Background Technology

[0002] Chirality is a fundamental property of nature, widely present in various substances. Chiral molecules that are mirror images of each other but cannot be superimposed are called enantiomers. In living systems, enantiomers with different configurations often exhibit distinct physiological and pharmacological activities. Accurate identification of enantiomers is crucial for ensuring drug safety and efficacy; therefore, chiral identification plays an irreplaceable role in drug development, disease diagnosis, and other fields. To achieve efficient chiral identification, techniques such as chromatography, spectroscopy, extraction, and electrochemical methods have been developed. While chromatography offers high separation efficiency and accuracy, its expensive equipment, complex operation, long analysis time, and requirement for professional personnel limit its widespread application in rapid on-site detection and large-scale deployment. Spectroscopy, such as circular dichroism spectroscopy, can directly provide optical activity information of chiral molecules, but its sensitivity is relatively low, posing challenges for detecting low-concentration samples. While fluorescence spectroscopy offers high sensitivity, it requires samples to possess fluorescent properties or be fluorescently labeled, increasing the complexity and cost of detection. Electrochemical chiral sensors have attracted much attention in recent years due to their advantages such as ease of operation, rapid response, and high sensitivity, and have provided great potential for breaking through difficulties and opening up new paths in the field of chiral analysis.

[0003] Metal-organic frameworks (MOFs) are highly crystalline hybrid materials formed by the self-assembly of metal ions or metal clusters with organic ligands through coordination bonds. Due to their high specific surface area, controllable porosity, and abundant nanostructures, they hold great promise for applications in gas separation, catalysis, and sensing. In recent years, MOF materials have attracted widespread attention in the field of chiral recognition. By introducing chiral organic ligands or post-modifying chiral guest molecules, MOF materials can be endowed with chiral recognition capabilities. However, single chiral MOF materials still have certain limitations in terms of recognition selectivity, sensitivity, and stability. To overcome the shortcomings of single MOF materials, researchers have proposed the concept of constructing MOF-on-MOF heterostructures. MOF-on-MOF heterostructures combine two or more different MOF materials through specific methods to form composite materials with unique structures and properties. This heterostructure combines the advantages of different MOF materials, producing a synergistic effect that significantly improves the chiral recognition performance, stability, and catalytic activity of the material. For example, by combining chiral MOF materials with different pore sizes and functions, selective recognition and separation of chiral molecules of different sizes and properties can be achieved. Although MOF-on-MOF heterostructures have great application potential in the field of chiral recognition, related research is still in its early stages. There are still many challenges in terms of material preparation methods, structural control and performance optimization. How to achieve effective composites between different MOF materials and improve the stability and accuracy of the materials are also urgent problems to be solved. Summary of the Invention

[0004] This invention provides a method for preparing and applying L-Ni-BDC / NM88B(Fe), an electrochemical chiral sensor material based on a chiral MOF-on-MOF heterostructure. This invention provides a simple and efficient innovative method for chiral recognition, promoting the development of this field.

[0005] The technical solution of this invention is as follows:

[0006] In the first aspect, a method for preparing L-Ni-BDC / NM88B(Fe), an electrochemical chiral sensor material based on a chiral MOF-on-MOF heterostructure, is disclosed, including the following steps:

[0007] 1) Preparation of NH2-MIL-88B(Fe): Ferric chloride hexahydrate, 2-aminoterephthalic acid (AAPD) and N,N-dimethylformamide (DMF) were mixed, NaOH solution was added and stirred evenly. After hydrothermal reaction, washing and drying, NH2-MIL-88B(Fe) was obtained.

[0008] 2) Preparation of Ni-BDC / NM88B(Fe): NH2-MIL-88B(Fe), nickel chloride hexahydrate, and terephthalic acid (TPA) were dispersed in a mixed solvent of water and N,N-dimethylacetamide (DMAC). After hydrothermal reaction and centrifugation, Ni-BDC / NM88B(Fe) was obtained.

[0009] 3) Carboxyl activation: Ni-BDC / NM88B(Fe) was dispersed in water with 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide EDC and N-hydroxysuccinimide NHS to prepare solution A by stirring.

[0010] 4) Preparation of L-Ni-BDC / NM88B(Fe): L-cysteine ​​(L-Cys) solution was added dropwise to solution A and reacted. L-cysteine ​​was introduced by amidation reaction. After filtration, washing and drying, L-Ni-BDC / NM88B(Fe) was obtained.

[0011] Preferably, the mass concentration of the NaOH solution in step 1) is 75-85 mg / mL.

[0012] Preferably, in step 1), the mass-to-volume ratio of ferric chloride hexahydrate, 2-aminoterephthalic acid, and DMF is (1.5-1.8) g: 1 g: (4.8-5.2) mL; the volume ratio of DMF to NaOH solution is 5:0.4; and the hydrothermal reaction is carried out at 90-110℃ for 10-16 h.

[0013] Preferably, in step 1), the sample after reaction is collected by centrifugation, washed sequentially with DMF, methanol and water, then dispersed in water and stirred overnight, centrifuged again, washed with methanol, and vacuum dried at 100-120℃ for 10-16h.

[0014] Preferably, in step 2), the volume ratio of water to DMAC is 1:1, and the mass ratio of NH2-MIL-88B(Fe), nickel chloride hexahydrate to terephthalic acid is 1:(1-1.1):(0.3-0.4); the hydrothermal reaction conditions in step 2) are 140-160℃ for 8-14h, and the product is collected by centrifugation after the reaction.

[0015] Preferably, in step 3), the mass ratio of Ni-BDC / NM88B(Fe) to EDC and NHS is 3.2:1, and the mass ratio of L-cysteine ​​to Ni-BDC / NM88B(Fe) is 3:(1-2).

[0016] Preferably, in step 4), the L-cysteine ​​(L-Cys) solution is added dropwise for 20-30 minutes, the reaction is carried out by stirring at room temperature for 3-5 hours, the sample is collected by filtration, washed with distilled water, and vacuum dried at room temperature for 10-16 hours.

[0017] Secondly, the application of the electrochemical chiral sensor material L-Ni-BDC / NM88B(Fe) based on the chiral MOF-on-MOF heterostructure is disclosed. It is used to prepare L-Ni-BDC / NM88B(Fe)-modified glassy carbon electrodes. The preparation method is as follows: a polished and cleaned bare glassy carbon electrode is placed in an aqueous solution of L-Ni-BDC / NM88B(Fe) with a concentration of 1.8–2 mg / mL. L-Ni-BDC / NM88B(Fe) is electrodeposited onto the electrode surface using cyclic voltammetry to obtain the L-Ni-BDC / NM88B(Fe) / GCE glassy carbon electrode. The cyclic voltammetry (CV) conditions are: scan potential from 0 to 1.0 V, scan rate of 50 mV / s. -1 Scan 50 times.

[0018] Preferably, for the chiral recognition of tryptophan isomers, the L-Ni-BDC / NM88B(Fe) / GCE electrode modified with L-Ni-BDC / NM88B(Fe) is placed in L-tryptophan and D-tryptophan aqueous solutions with a concentration of 4.5-5 mmol / L, respectively. The chiral recognition of tryptophan isomers is performed using differential pulse voltammetry: the one with a higher peak current value is L-tryptophan, and the one with a lower peak current value is D-tryptophan. The specific conditions for differential pulse voltammetry (DPV) are: the scan potential ranges from -0.4 to 1.2 V.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] This invention employs a hydrothermal method to couple Ni-BDC with NH2-MIL-88B(Fe) to prepare MOF-on-MOF heterostructure nanosheets containing unique interfacial chemical bonds. Further post-synthetic modification introduces chiral cysteine ​​to obtain L-Ni-BDC / NM88B(Fe). The stable Ni-O-Fe bonds formed at the interface promote electron transfer and lower the reaction energy barrier. Electrochemical tests show that its recognition efficiency for L / D-tryptophan reaches 3.05. Attached Figure Description

[0021] Figure 1 This is a transmission electron microscope image of L-Ni-BDC / NM88B(Fe) prepared in Example 1 of this invention.

[0022] Figure 2 These are the cyclic voltammetry curves of Ni-BDC / GCE, NM88B(Fe) / GCE and L-Ni-BDC / NM88B(Fe) / GCE of the present invention.

[0023] Figure 3This is a DPV diagram of the recognition of tryptophan isomers by L-Ni-BDC / NM88B(Fe) / GCE of the present invention. Detailed Implementation

[0024] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions will be clearly and completely described below in conjunction with the embodiments of this invention.

[0025] Example 1

[0026] The preparation method of the electrochemical chiral sensor material L-Ni-BDC / NM88B(Fe) based on the chiral MOF-on-MOF heterostructure is as follows:

[0027] 1) Preparation of NH2-MIL-88B(Fe): Weigh 2g of sodium hydroxide, dissolve it in ultrapure water, transfer it to a 25mL volumetric flask, make up to volume, and shake well to obtain a NaOH solution with a mass concentration of 80mg / mL for later use.

[0028] Weigh 0.2703 g of ferric chloride hexahydrate, 0.1661 g of 2-aminoterephthalic acid, and 5 mL of N,N-dimethylformamide (DMF) and place them in a reaction vessel. Add 0.4 mL of NaOH solution while stirring at room temperature until the mixture is homogeneous. React hydrothermally at 100 °C for 12 h. After cooling, centrifuge the sample, wash twice with DMF, twice with methanol, and then wash with a large amount of water. Transfer the sample to 400 mL of ultrapure water and stir overnight. Centrifuge again, wash twice with methanol, and dry under vacuum at 110 °C for 12 h to obtain NH2-MIL-88B(Fe).

[0029] 2) Preparation of Ni-BDC / NM88B(Fe): Weigh 30 mL of ultrapure water and 30 mL of N,N-dimethylacetamide (DMAC) and place them in a reaction vessel. Add 0.9507 g of nickel chloride hexahydrate, 0.3323 g of terephthalic acid and 0.9 g of NH2-MIL-88B(Fe). After stirring, react hydrothermally at 150 °C for 10 h. Collect the sample by centrifugation to obtain the Ni-BDC / NM88B(Fe) heterostructure.

[0030] 3) Preparation of L-Ni-BDC / NM88B(Fe): Weigh 0.16g Ni-BDC / NM88B(Fe), 0.05g EDC, 0.05g NHS and 50mL distilled water, stir at room temperature for 2h to prepare solution A; weigh 0.3g L-cysteine ​​and dissolve in 8mL distilled water to prepare solution B. Add solution B to solution A within 30min, stir at room temperature for 4h, collect the sample by filtration, wash 3 times with distilled water, and vacuum dry at room temperature for 12h to obtain the composite material L-Ni-BDC / NM88B(Fe).

[0031] Figure 1This is a transmission electron microscope (TEM) image of L-Ni-BDC / NM88B(Fe), a chiral recognition material based on a chiral MOF-on-MOF heterostructure. Figure 1 The low-magnification TEM image of a shows that L-Ni-BDC / NM88B(Fe) has a nanosheet structure with a size of about 500 nm, which vividly presents the macroscale characteristics of the material. Figure 1 High-resolution transmission electron microscopy (HRTEM) images of b show that the material has a layered stacked structure, which is beneficial for electron transport and is an important factor in improving the material's performance; through further analysis... Figure 1 c and Figure 1 The cross-sectional analysis of the lattice fringes in the image shows that the alternating bright and dark fringes correspond to Ni-BDC and NH2-MIL88B(Fe), respectively, confirming the successful construction of the heterojunction structure at the microscopic level. This ordered structure endows the material with unique physicochemical properties and enhances interfacial electron transfer capabilities. Combined with transmission electron microscopy characterization results, this indicates that a sensing material based on a chiral MOF-on-MOF heterostructure has been successfully prepared.

[0032] Example 2

[0033] The preparation method of the electrochemical chiral sensor material L-Ni-BDC / NM88B(Fe) based on the chiral MOF-on-MOF heterostructure is as follows:

[0034] 1) Preparation of NH2-MIL-88B(Fe): Weigh 2g of sodium hydroxide, dissolve it in ultrapure water, transfer it to a 25mL volumetric flask, make up to volume, and shake well to obtain a NaOH solution with a mass concentration of 80mg / mL for later use.

[0035] Weigh 0.2703 g of ferric chloride hexahydrate, 0.1661 g of 2-aminoterephthalic acid, and 5 mL of N,N-dimethylformamide (DMF) and place them in a reaction vessel. Add 0.4 mL of NaOH solution while stirring at room temperature until the mixture is homogeneous. React hydrothermally at 110 °C for 10 h. After cooling, centrifuge the sample, wash twice with DMF, twice with methanol, and then wash with a large amount of water. Transfer the sample to 400 mL of ultrapure water and stir overnight. Centrifuge again, wash twice with methanol, and dry under vacuum at 100 °C for 16 h to obtain NH2-MIL-88B(Fe).

[0036] 2) Preparation of Ni-BDC / NM88B(Fe): Weigh 30 mL of ultrapure water and 30 mL of N,N-dimethylacetamide (DMAC) and place them in a reaction vessel. Add 0.9507 g of nickel chloride hexahydrate, 0.3323 g of terephthalic acid and 0.9 g of NH2-MIL-88B(Fe). After stirring, react hydrothermally at 140 °C for 12 h. Collect the sample by centrifugation to obtain the Ni-BDC / NM88B(Fe) heterostructure.

[0037] 3) Preparation of L-Ni-BDC / NM88B(Fe): Weigh 0.16g Ni-BDC / NM88B(Fe), 0.05g EDC, 0.05g NHS and 50mL distilled water, and stir at room temperature for 2h to prepare solution A; weigh 0.3g L-cysteine ​​and dissolve in 8mL distilled water to prepare solution B. Add solution B to solution A within 20min, stir at room temperature for 3h, collect the sample by filtration, wash 3 times with distilled water, and vacuum dry at room temperature for 16h to obtain the composite material L-Ni-BDC / NM88B(Fe).

[0038] Comparative Example 1

[0039] In this comparative example, a single MOF material NH2-MIL-88B(Fe) was used, and the preparation method was the same as step 1) of Example 1.

[0040] Comparative Example 2

[0041] In this comparative example, a single MOF material, Ni-BDC, was used. The preparation method was as follows: 30 mL of ultrapure water and 30 mL of N,N-dimethylacetamide (DMAC) were weighed and placed in a reaction vessel. 0.9507 g of nickel chloride hexahydrate and 0.3323 g of terephthalic acid were added. After stirring, the mixture was hydrothermally reacted at 150 °C for 10 h. The sample was collected by centrifugation to obtain the Ni-BDC heterostructure.

[0042] Comparative Example 3

[0043] In this comparative example, no chiral modification of the material is performed. The material used is Ni-BDC / NM88B(Fe), and the preparation method includes steps 1) and 2) in the examples.

[0044] Comparative Example 4

[0045] In this comparative example, D-cysteine ​​was used to replace L-cysteine ​​in Example 1, and the rest of the preparation methods and steps were the same as in Example 1, to prepare D-Ni-BDC / NM88B(Fe).

[0046] Electrode fabrication and cyclic voltammetry testing were performed on the materials obtained in Example 1 and Comparative Examples 1-4, as detailed below:

[0047] Bare glassy carbon electrodes (GCEs) were polished on chamois leather with 0.3 μm and 0.05 μm Al2O3, respectively. After washing away surface contaminants, they were ultrasonicated in ethanol and ultrapure water for 5 min each. Then, the bare glassy carbon electrodes were placed in solutions of NH2-MIL-88B(Fe) prepared in Comparative Example 1, Ni-BDC / NM88B(Fe) prepared in Comparative Example 3, D-Ni-BDC / NM88B(Fe) prepared in Comparative Example 4, and L-Ni-BDC / NM88B(Fe) prepared in Example 1, respectively. Cyclic voltammetry was used to electrodeposit these solutions onto the surface of the glassy carbon electrodes, preparing Ni-BDC / GCE, NH2-MIL-88B(Fe) / GCE, Ni-BDC / NM88B(Fe) / GCE, D-Ni-BDC / NM88B(Fe) / GCE, and L-Ni-BDC / NM88B(Fe) / GCE.

[0048] The prepared NH2-MIL-88B(Fe) / GCE, Ni-BDC / NM88B(Fe) / GCE, D-Ni-BDC / NM88B(Fe) / GCE and L-Ni-BDC / NM88B(Fe) / GCE were respectively placed in 5.0 mM [Fe(CN)6] 4- / 3- Cyclic voltammetry (CV) was performed on the solution (containing 0.1 M KCl) with a scan range of -0.2 to 0.6 V and a scan rate of 50 mV·s. -1 In a single scan, redox peaks appeared on the electrode surface, indicating that the chemical reaction on the electrode surface is nearly reversible. Cyclic voltammetry curves for different electrodes are shown below. Figure 2 As shown in the figure. The test results show that the peak current order is: L-Ni-BDC / NM88B(Fe) / GCE > D-Ni-BDC / NM88B(Fe) / GCE > Ni-BDC / NM88B(Fe) / GCE > NH2-MIL-88B(Fe) / GCE. This is attributed to the high electronic activity and large active area of ​​L-Ni-BDC / NM88B(Fe) due to its electron selectivity effect, resulting in the largest peak current. This indicates that it can be used as an electrochemical chiral sensor for tryptophan isomer recognition.

[0049] The construction of an electrochemical chiral sensor and the identification of tryptophan isomers are detailed below:

[0050] The bare glassy carbon electrode was polished on chamois leather with 0.3 μm and 0.05 μm Al2O3, respectively. After washing away surface contaminants, it was transferred to ethanol and ultrapure water and sonicated for 5 min each. Then, the clean electrode was placed in a 2 mg / mL solution of L-Ni-BDC / NM88B(Fe) prepared in Example 1, and L-Ni-BDC / NM88B(Fe) was electrodeposited onto the electrode surface using cyclic voltammetry (CV): the scan potential ranged from 0 to 1.0 V, and the scan rate was 50 mV / s. -1 After scanning 50 times, an electrode modified with L-Ni-BDC / NM88B(Fe) was obtained.

[0051] The L-Ni-BDC / NM88B(Fe) modified electrode was placed in 25 mL of L-tryptophan and D-tryptophan solutions of 4–5 mmol / L, respectively. The chiral recognition of the tryptophan isomer was performed by differential pulse voltammetry (DPV) with a scan potential of -0.4 to 1.2 V. Figure 3 The image shows the DPV (Dynamic Current Variation) plot for the recognition of tryptophan isomers. It can be seen that the peak current values ​​differ when tryptophan isomers (L-tryptophan and D-tryptophan) interact with L-Ni-BDC / NM88B(Fe) / GCE. This is likely because D-tryptophan has stronger hydrogen bonding and π-π interactions with L-Ni-BDC / NM88B(Fe), leading to more D-tryptophan adsorption on the L-Ni-BDC / NM88B(Fe) / GCE electrode surface, resulting in decreased conductivity. Consequently, the peak current decreases more when recognizing D-tryptophan, indicating that this chiral recognition material has a stronger recognition signal for L-tryptophan. Therefore, L-tryptophan in the tryptophan isomer can be rapidly and sensitively identified.

[0052] Although the present invention has been described in detail by way of preferred embodiments, the invention is not limited thereto. Various equivalent modifications or substitutions can be made to the embodiments of the present invention by those skilled in the art without departing from the spirit and essence of the invention, and such modifications or substitutions should all be within the scope of the invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing L-Ni-BDC / NM88B(Fe), an electrochemical chiral sensor material based on a chiral MOF-on-MOF heterostructure, characterized in that, Includes the following steps: 1) Preparation of NH2-MIL-88B(Fe): Ferric chloride hexahydrate, 2-aminoterephthalic acid AAPD and N,N-dimethylformamide DMF were mixed, NaOH solution was added and stirred evenly. After hydrothermal reaction, washing and drying, NH2-MIL-88B(Fe) was obtained. 2) Preparation of Ni-BDC / NM88B(Fe): NH2-MIL-88B(Fe), nickel chloride hexahydrate, and terephthalic acid TPA were dispersed in a mixed solvent of water and N,N-dimethylacetamide DMAC. After hydrothermal reaction and centrifugation, Ni-BDC / NM88B(Fe) was obtained. 3) Carboxyl activation: Ni-BDC / NM88B(Fe) was dispersed in water with 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide EDC and N-hydroxysuccinimide NHS to prepare solution A by stirring. 4) Preparation of L-Ni-BDC / NM88B(Fe): L-cysteine ​​(L-Cys) solution was added dropwise to solution A and reacted. After filtration, washing and drying, L-Ni-BDC / NM88B(Fe) was obtained.

2. The preparation method of L-Ni-BDC / NM88B(Fe) electrochemical chiral sensor material based on chiral MOF-on-MOF heterostructure as described in claim 1, characterized in that, In step 1), the mass concentration of the NaOH solution is 75-85 mg / mL.

3. The preparation method of L-Ni-BDC / NM88B(Fe) electrochemical chiral sensor material based on chiral MOF-on-MOF heterostructure as described in claim 1, characterized in that, In step 1), the mass-to-volume ratio of ferric chloride hexahydrate, 2-aminoterephthalic acid, and DMF is (1.5-1.8) g: 1 g: (4.8-5.2) mL; the volume ratio of DMF to NaOH solution is 5:0.4; and the hydrothermal reaction is carried out at 90-110℃ for 10-16 h.

4. The preparation method of L-Ni-BDC / NM88B(Fe) electrochemical chiral sensor material based on chiral MOF-on-MOF heterostructure as described in claim 1, characterized in that, In step 1), the sample after reaction is collected by centrifugation, washed sequentially with DMF, methanol and water, then dispersed in water and stirred overnight, centrifuged again and washed with methanol, and then vacuum dried at 100-120℃ for 10-16h.

5. The preparation method of L-Ni-BDC / NM88B(Fe) electrochemical chiral sensor material based on chiral MOF-on-MOF heterostructure as described in claim 1, characterized in that, In step 2), the volume ratio of water to DMAC is 1:1, and the mass ratio of NH2-MIL-88B(Fe), nickel chloride hexahydrate to terephthalic acid is 1:(1-1.1):(0.3-0.4). The hydrothermal reaction conditions in step 2) are 140-160℃ for 8-14 hours, and the product is collected by centrifugation after the reaction.

6. The preparation method of L-Ni-BDC / NM88B(Fe) electrochemical chiral sensor material based on chiral MOF-on-MOF heterostructure as described in claim 1, characterized in that, In step 3), the mass ratio of Ni-BDC / NM88B(Fe) to EDC and NHS is 3.2:1, and the mass ratio of L-cysteine ​​to Ni-BDC / NM88B(Fe) is 3:(1-2).

7. The method for preparing the electrochemical chiral sensor material L-Ni-BDC / NM88B(Fe) based on a chiral MOF-on-MOF heterostructure as described in claim 1, characterized in that, In step 4), the L-cysteine ​​solution is added dropwise over 20-30 minutes, and the reaction is carried out with stirring at room temperature for 3-5 hours. The sample is then collected by filtration, washed with distilled water, and vacuum dried at room temperature for 10-16 hours.

8. The application of the sensor material prepared by the method for preparing the electrochemical chiral sensor material L-Ni-BDC / NM88B(Fe) based on the chiral MOF-on-MOF heterostructure as described in any one of claims 1-7, characterized in that, The method for preparing L-Ni-BDC / NM88B(Fe) modified glassy carbon electrode is as follows: a polished and cleaned bare glassy carbon electrode is placed in an aqueous solution of L-Ni-BDC / NM88B(Fe) with a concentration of 1.8-2 mg / mL, and L-Ni-BDC / NM88B(Fe) is electrodeposited on the electrode surface by cyclic voltammetry to obtain the L-Ni-BDC / NM88B(Fe) / GCE modified glassy carbon electrode.

9. The application of the sensor material prepared by the preparation method of L-Ni-BDC / NM88B(Fe) based on the chiral MOF-on-MOF heterostructure as described in claim 8, characterized in that, For chiral recognition of tryptophan isomers, specifically, L-Ni-BDC / NM88B(Fe) / GCE electrodes modified with L-Ni-BDC / NM88B(Fe) were placed in aqueous solutions of L-tryptophan and D-tryptophan with concentrations of 4.5–5 mmol / L, respectively. Differential pulse voltammetry was used to identify the chiral isomers of tryptophan: the one with the higher peak current value was L-tryptophan, and the one with the lower peak current value was D-tryptophan.